Heat Exchanger Network Optimization in A Natural Gas Dehydration Unit - Kurniawan, Adhi; Juwari, Juwari; Handogo, Renanto (Institut Teknologi Sepuluh Nopember, 2020)
A dehydration unit using triethylene glycol absorption is a common process in natural gas processing. In its regeneration section, the regenerated lean glycol needs to be cooled before entering the glycol absorber, while the rich glycol is to be preheated before entering the regenerator. This is a good candidate for heat exchanger network (HEN) optimization. In this work, the HEN was revisited using pinch analysis (PA) and mathematical programming (MP) using superstructure. The optimized networks were evaluated using simplified total annual cost (TAC). The PA method using small ï„Tmin (minimum temperature approach) led to the configuration of three exchangers, a heater and a cooler, with minimized utilities. At larger ï„Tmin, the configuration became into two exchangers, two heaters, and a cooler. The minimum calculated TAC is 60,351/year at ï„Tmin = 12.5oC. Furthermore, it was revealed that one heater and one exchanger were two small. Therefore, they were omitted, and the heat load were redistributed to the network. The calculated TAC became 59,224/year. The superstructure approach resulted in two exchangers, a heater, and a cooler; with a calculated minimum TAC of 57,597/year. The two approaches have resulted in very similar minimized TAC.